The Influence of Leadership, Organizational Culture, Quality of Human Resources and Communication on Organizational Performance - Deti Nuryati (Jurnal Syntax Transformation, 2023)
The background to this research is that there is a problem with organizational performance at the Information Communication and Statistics Service, West Bandung Regency, West Java Province, which is not yet optimal. Organizational performance problems are caused by a lack of influence of leadership, organizational culture, quality of human resources and communication on organizational performance. This research aims to determine the influence of leadership, organizational culture, quality of Human Resources and communication on organizational performance, both partially and jointly. The sampling technique in this research was proportional stratified random sampling with a sample of 102 respondents. This research method is included in the type of explanatory research which uses a quantitative approach. Data collection techniques use questionnaire techniques, literature study. The data collection tool for this research is a questionnaire based on a Likert scale. The data analysis technique in this research is validity test, reliability test, normality test, linearity test, multicollinearity test, heteroscedasticity test, F test and t test, simple and multiple linear regression. The research results prove that there is a significant and positive influence on organizational performance. First, there is an influence of leadership on organizational performance of 54.8%. Second, there is an influence of organizational culture on organizational performance of 55.2%. Third, there is an influence of the quality of Human Resources on organizational performance of 50.5%. Fourth, there is an influence of communication on organizational performance of 56.8%. And fifth, there is the influence of leadership, organizational culture, quality of Human Resources and Communication together on organizational performance of 70.8%. As a recommendation from the results of this research, organizational performance at the West Bandung Regency Communication, Information and Statistics Service can be achieved through the influence of leadership, organizational culture, quality of Human Resources and Communication. These four variables must be considered, so that organizational performance can increase.